2006
DOI: 10.1099/mic.0.28941-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids from freshwater environments capable of IncQ retrotransfer are diverse and include pQKH54, a new IncP-1 subgroup archetype

Abstract: Nine mercury-resistance plasmids isolated from river epilithon were assessed for their ability to retrotransfer the non-conjugative IncQ plasmid, R300B, derivatives of which have commercial uses that may result in accidental or deliberate release into the environment. Retrotransfer frequencies ranging from 2?1610 "4 to 1?75610 "5 were obtained for five of the nine plasmids -the remaining plasmids showed low or undetectable retrotransfer ability. The majority of the retrotransfer-proficient plasmids could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 88 publications
0
46
0
Order By: Relevance
“…This was observed in conjugation assays with a P. putida strain as plasmid donor (Haines et al, 2006). By comparing genomic signatures between whole plasmid genome sequences and bacterial chromosomes we previously showed that pQKH54 had the highest genomic signature similarity to three Pseudomonas chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was observed in conjugation assays with a P. putida strain as plasmid donor (Haines et al, 2006). By comparing genomic signatures between whole plasmid genome sequences and bacterial chromosomes we previously showed that pQKH54 had the highest genomic signature similarity to three Pseudomonas chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This 70 kb plasmid encodes mercury resistance as the only reported accessory trait and was captured from river epilithon in Wales by an exogenous plasmid isolation method (Haines et al, 2006). The authors defined the IncP-1c subgroup based on clear divergence of the plasmid's backbone genes from the wellcharacterized plasmids of the IncP-1a and IncP-1b subgroups (Haines et al, 2006;Norberg et al, 2011). Here we describe the first multi-drug resistance plasmid in this IncP-1c subgroup, pKS208, as well as the first cryptic plasmid, pMBUI1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations